Dari Jabariyah, ke Qadariyah, hingga Islam Progresif: Respons Muslim atas Wabah Corona di Indonesia - Nur Hidayah (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
Abstract:WHO, The United Nation Health Agency, has declared COVID-19 as a global pandemic. The Indonesian government has issued some measures and policies to deal with this outbreak. Various elements of civil society have also been moving to deal with this pandemic. As the largest Muslim country, a question arises as to what extent Islam plays a role in tackling this corona outbreak. By analyzing the various responses of the Muslim community, based on primary and secondary data, this paper argues that Indonesian Muslims are polarized in responding to the COVID-19 pandemic. The spectrum extends from the 'fear zone' which considers this outbreak as having prevented them from worshiping God, to the 'learning zone', which is the majority, by accepting this outbreak as a disaster and attributing its cause to human actions damaging nature, to the 'growth zone' which takes active role in dealing with the outbreak. This diversity is influenced by the different theological believes spanning from the Jabbariyah to Qadariyah to Progressive Islam. The influence of Jabbariyah's theology leads to the attitudes of fatalism, while the influence of the Qadariyah theology leads to the attitude of accepting the plague as a disaster and attributing this pandemic to human’s excessive exploitation of nature. The influence of progressive Islamic theology leads to the flexibility of Islamic interpretations rooted in the concept of Maqasid Sharia to prioritize harm prevention over seeking benefits and Islamic teaching of amar ma'ruf nahyi munkar as a religion playing active role in social transformation.Keywords: Indonesia, Islam, Muslims, Pandemic, COVID-19, Jabbariyah, Qadariyah, Progressive Islam. Abstrak:WHO, lembaga kesehatan PBB, telah menetapkan COVID-19 sebagai pandemi global. Pemerintah Indonesia mengambil serangkaian kebijakan untuk menanggulangi wabah ini. Berbagai elemen masyarakat sipil bergerak untuk membantu menanggulangi pandemi ini. Sebagai negara Muslim terbesar, timbul pertanyaan sejauh mana Islam memainkan peran dalam penanggulangan wabah corona ini. Dengan menganalisa berbagai respon komunitas Muslim terhadap wabah ini berdasarkan data primer dan sekunder, paper ini berargumen bahwa Muslim Indonesia terpolarisasi dalam merespon pandemi COVID-19 ini. Spektrum response ini terbentang dari ‘fear zone’ yang menganggap wabah ini telah menghalangi mereka dari beribadah kepada Allah, kepada ‘learning zone’ yang merupakan mayoritas dengan menerima wabah ini sebagai musibah dan teguran atas perbuatan manusia merusak alam, hingga ‘growth zone’ yang mengambil peran aktif untuk menangani wabah. Keragaman ini dilatari oleh perbedaan pengaruh teologis yang dianutnya dari spektrum Jabbariyah ke Qadariyah hingga Islam Progresif. Pengaruh teologi Jabbariyah membawa kepada sikap fatalisme, sedangkan pengaruh teologi Qadariyah membawa kepada sikap menerima wabah sebagai musibah dan mengatributkan pandemi kepada kesalahan manusia mengelola alam. Pengaruh teologi Islam progresif membawa pada kelenturan penafsiran Islam yang berakar pada konsep Maqasid Syariah untuk mendahulukan pencegahan madharat ketimbang pencarian maslahat dan ajaran amar ma’ruf nahyi munkar Islam sebagai agama yang aktif melakukan transformasi sosial.Kata Kunci: Indonesia, Islam, Muslim, Pandemi, COVID-19, Jabbariyah, Qadariyah, Islam Progresif